Scientific contagion heuristic: Judgments about the acceptability of water for religious use after potential scientific treatment - Sumitava Mukherjee; Payel C. Mukherjee (Judgment and Decision Making, 2022)
We propose the concept of ‘scientific contagion’ --- a mental heuristic through which any form of scientific treatment transfers some essence of ‘science’ to the processed substance, thereby affecting its nature and social acceptability. This was tested regarding the potential treatment of water from natural sources before it is used for religious purposes, as many such sources have dangerous pollutants. For an ancient natural well having a religious narrative, most participants judged that the acceptability of water would be reduced for religious purposes but not for drinking if local officials scientifically treat the water. That is not the case if religious rituals are conducted on the water instead (Study 1). If water from a “holy river” is processed scientifically, most participants predicted that it would reduce acceptability for religious use while increasing acceptability for drinking (Study 2). Potential scientific treatment without altering the composition of water from a natural spring also decreased acceptability for religious use but there was no effect on acceptability for drinking or on willingness to pay money for the water (Study 3). A follow-up study comparing acceptability for different kinds of water sources --- from a holy well, natural spring, and household tap water sourced from either underground wells or rivers found lower acceptability for religious usage compared to drinking after potential scientific treatment for all these waters, but more so for holy and natural waters (Study 4). These studies establish the phenomena of scientific contagion that could have significant social implications and open future directions.